Nutritional Status among Children Aged 6-23 Months and Associated Factors in Dalits and Non-Dalits of Dhanusha District, Nepal : A Cross-Sectional Comparative Study. - Sah_Anil, Kumar. (Tufts University. Tisch Library., 2019)
This poster identifies the nutritional status and its associated factors among children 6-23 months in Dalits and Non-Dalits of Dhanusha district, Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy